2023
DOI: 10.1186/s40001-023-01252-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and short-term outcomes of acute pancreatitis among patients with COVID-19

Abstract: Objective The existing literature on the combination of acute pancreatitis (AP) and COVID-19 is scarce. The objective of our study is to compare the clinical outcomes and occurrence of long COVID syndrome in AP patients with and without COVID-19, while investigating the potential impact of COVID-19 on the severity, mortality rate, and long COVID syndrome in these patients. Methods This retrospective, observational study was conducted at a single ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, the authors believe that these differences were probably due to restrictive measures implemented during the pandemic period, consequent delay in care, and a restriction on surgical treatment indications [34]. Conversely, a more recent study directly compared SARS-CoV-2-positive patients and SARS-CoV-2-negative patients, both diagnosed with AP, and it found no differences regarding mortality rate, severity, or sequelae [35].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the authors believe that these differences were probably due to restrictive measures implemented during the pandemic period, consequent delay in care, and a restriction on surgical treatment indications [34]. Conversely, a more recent study directly compared SARS-CoV-2-positive patients and SARS-CoV-2-negative patients, both diagnosed with AP, and it found no differences regarding mortality rate, severity, or sequelae [35].…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, retrospective research conducted in Spain indicated a potential correlation between COVID‐19 and a decreased likelihood of AP 28 . A retrospective investigation conducted at a single facility in Sichuan, China, revealed that COVID‐19 did not increase the severity or fatality rates among individuals diagnosed with pancreatitis 29 . According to retrospective research conducted in South Korea, it was shown that the incidence of AP increased in individuals who contracted COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals frequently report experiencing significant fatigue, even when engaging in minimal levels of physical or cognitive activity. The presence of fatigue may be accompanied by a widespread feeling of malaise and a decreased ability to participate in previously habitual activities [ 5 ]. Cognitive impairments, commonly known as "brain fog," are frequently reported by individuals with long COVID.…”
Section: Reviewmentioning
confidence: 99%